PROSES PERENCANAAN KESELURUHAN PENGEMBANGAN AGROWISATA PADA DESA KUTANAGARA KECAMATAN MALANGBONG KABUPATEN GARUT - Dalen Darbec Anew; Mas Halimah (Universitas Nasional, 2024)
ABSTRACT The tourism industry is pivotal for regional development, fostering community welfare, job creation, and increasing local income. Agrotourism, blending agriculture, natural beauty, and cultural interaction, stands out as a popular and promising form of tourism. This study examines agrotourism in Kutanagara village, Garut Regency, focusing on planning and development by the Village Government through Village-Owned Enterprises (BUMDes). Utilizing a qualitative approach with a descriptive method, data was collected via interviews and observations involving key informants. The research centers on the five planning stages for agrotourism development, aiming to boost tourist numbers, revitalize the local economy, and enhance the Village's Original Income (PAD). Results indicate Kutanagara Village successfully mapped agrotourism potential with an Agrotourism Master Plan, yet challenges persist regarding objective clarity, planning process effectiveness, and community participation. Successful agrotourism development necessitates meticulous planning a ABSTRACT The tourism industry is pivotal for regional development, fostering community welfare, job creation, and increasing local income. Agrotourism, blending agriculture, natural beauty, and cultural interaction, stands out as a popular and promising form of tourism. This study examines agrotourism in Kutanagara village, Garut Regency, focusing on planning and development by the Village Government through Village-Owned Enterprises (BUMDes). Utilizing a qualitative approach with a descriptive method, data was collected via interviews and observations involving key informants. The research centers on the five planning stages for agrotourism development, aiming to boost tourist numbers, revitalize the local economy, and enhance the Village's Original Income (PAD). Results indicate Kutanagara Village successfully mapped agrotourism potential with an Agrotourism Master Plan, yet challenges persist regarding objective clarity, planning process effectiveness, and community participation. Successful agrotourism development necessitates meticulous planning and active community engagement. This research contributes to Public Administration science, offering practical insights for the Kutanagara Village Government. By leveraging agrotourism potential, the goal is to elevate the Village's Original Income (PAD) and local community welfare, serving as a guide for Garut Regency in optimizing the tourism sector, especially in rural areas. Key word: Agrotourism, Planning, Public Management, Village Government, Village’s Original Income, Village-Owned Enterprises (BUMDes).nd active community engagement. This research contributes to Public Administration science, offering practical insights for the Kutanagara Village Government. By leveraging agrotourism potential, the goal is to elevate the Village's Original Income (PAD) and local community welfare, serving as a guide for Garut Regency in optimizing the tourism sector, especially in rural areas. Key word: Agrotourism, Planning, Public Management, Village Government, Village’s Original Income, Village-Owned Enterprises (BUMDes).